Patent search and analysis supporting technology innovation - Bin LIU; Ling FENG; Fei WANG; Zhi-yong PENG (Tongxin xuebao)
The main research work of patent search and analysis were summarizes.The patent search includes patentabil-ity search,prior art search,and query expansion.And the patent analysis includes patent map,novelty analysis,and a new analysis framework named PatentDom.Finally,based on the idea of deep learning,three new methods of patent search and analysis are put forward.